2016
DOI: 10.1080/14767724.2016.1195729
|View full text |Cite
|
Sign up to set email alerts
|

‘Responsibility in mobility’: international students and social responsibility

Abstract: Enhancing the educational experience and social connectedness for international students is the responsibility of different involved parties among whom international students themselves and host institutions play a key role. However, the question of how the condition of crossborder mobility has shaped and re-shaped international students' responsibility towards the home and host country and other social relationships that have been formed via their mobility experiences is often neglected. This paper examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Furthermore, in a recent study, Tran and Vu (2017) suggested the need to see international students as also bearers of responsibilities in addition to rights-a perspective seldom explored so far. Indeed, in considering ISM ethics and politics, one must resist the tendency to assume international students to be always the victims (see Baas, 2014).…”
Section: Concepts For Further Thinking Ism Ethics and Politicsmentioning
confidence: 99%
“…Furthermore, in a recent study, Tran and Vu (2017) suggested the need to see international students as also bearers of responsibilities in addition to rights-a perspective seldom explored so far. Indeed, in considering ISM ethics and politics, one must resist the tendency to assume international students to be always the victims (see Baas, 2014).…”
Section: Concepts For Further Thinking Ism Ethics and Politicsmentioning
confidence: 99%
“…Particularly, Sam's reflections on the host culture in comparison with his home culture echo the finding from Scharoun () that educational outbound mobility to a significantly different culture can enhance cultural awareness of both the other culture and one's own culture. Awareness of cultural idiocrasies and the gaps between the two cultures is sequentially conducive to fostering intercultural sensitivity, self‐awareness (Bretag & van der Veen, ; Campbell & Walta, ) and intercultural capital's exchange value in transnational mobility (Tran & Pham, ; Tran & Vu, , ). According to Scharoun (), this benefit would not be possible when students conducted a study tour in like‐minded OECD countries, such as the United States, the UK and Canada.…”
Section: Research Findingsmentioning
confidence: 99%
“…Our study (conducted in 2018) explored 37 women’s educational biographies as international and refugee-background students in two universities: 21 in Aotearoa New Zealand (NZ) and 16 in Bangladesh. Our work adds to the growing body of scholarship focused on questions of ethics, care and responsibility in, and in relation to, internationalised HE (Madge et al, 2015 ; Raghuram et al, 2009 ; Madge et al, 2009 ; Tran and Vu, 2017 ). It also adds to scholarship which contests representations of refugee-background students solely in terms of trauma or difficulty (Vickers et al, 2017 ), while recognising how hard borders are entrenched and re-entrenched through structural and everyday practices that alienate (Lambrechts, 2020 ; Tofighian, 2018 ).…”
Section: Introductionmentioning
confidence: 86%